Theory - Practice - Ethics: Is there a Gap? A Unique Concept to Reflect on - Mortell, Manfred (Acta Scientific, 2020)
This article will discuss a unique concept which the author calls the “theory-practice-ethics gap”. It advises the reader of the existing healthcare dilemmas related to medical errors which endangers a patient’s safety. The predicament is one of non-compliance or unethical practices by healthcare professionals. Predictably, the healthcare academics declare that when clinical practice is lacking, a “theory-practice gap” is typically to blame. Within this paradigm there is a gap between theoretical knowledge and its appliance in practice. Testimony relating to the non-integration of theory and practice makes the conjecture that environmental dynamics are accountable and will affect learning and practice results, hence the "gap". Nevertheless, it is the author's credence, that to "bridge the gap" relating to theory and practice an additional factor must be taken into account. The factor is called “Ethics” and introduces a unique concept which the author has labelled the “theory-practice-ethics gap”. This unique concept must be considered when appraising the undesirable consequences of medical errors in healthcare practice.